Mechanical and physical properties of laser sintered nanocomposite containing organic and inorganic fillers: a context review - Nwangwu , Uchechukwu; Obiukwu, Osita; Ambhore, Nitin (Vietnam Journal of Science and Technology, 2025)
Laser-sintered nanocomposites have attracted many researchers in the automotive, military, and medical industries. This makes it simple to produce intricate parts with superior mechanical performance. Nowadays, nanocomposite has become an economical way to fabricate materials with a low cost, considerable weight, and improved mechanical and physical properties. This paper reviewed the physical and mechanical characteristics of nanocomposite materials. Organic and inorganic filler compounds and their effect on mechanical properties have been discussed. It is seen that nanosized materials perform better than counterpart materials; these materials have much potential in the engineering and medical fields. Much research has been conducted on the incorporation of organic and inorganic fillers on the performance of nanocomposite. Numerous studies have shown that adding nanofiller results in significant improvements and enhancements in the mechanical properties of natural composites. The incorporation of nanofiller materials in small percentages into the matrix makes the weight of nanocomposites lighter than conventional composite. Different factors such as dispersion rate and moisture absorption of nano-filler, and their effect on flexural strength, fracture toughness, and hardness of the nanocomposite have been reported.